Vivências do eu-baobá em Educação Antirracista numa escola pública municipal em Açailândia - Maranhão - SOUSA, Fausto Ricardo Silva (2022)
The present dissertation, “Experiences of the me-baobab in anti-racist education in a municipal public school in Açailândia-Maranhão”, it is the materialization of a trajectory of concerns facing the Brazilian educational reality hostile to the black body and of afro-diasporic counter hegemonic learning. Having as object the anti-racist education beyond the disciplinary point of view and bringing the school routine to the discussion, the paper is justified by the complex problem-situation of the racist structure that dynamizes brazilian society, conditioning the spaces that the Afro-descendant population can occupy, and by the understanding that anti racism, which categorizes the Black Movement's activities, underpins the African and Afro brazilian knowledge of resistance and enables educational restructuring. Thus, understanding how racism is being dealt with in the daily life of an elementary school in the city of Açailândia Maranhão is the concern that underlies my construction. The objective that guides the study is "To analyze the confrontation with racism in the school routine in an elementary school in the city of Açailândia - Maranhão for the construction of an Anti-racist Education" which in this dissertation is an element articulated to the counter-hegemonic struggle of the Black Movement, as well as “Writing/Living stories of the me-baobab intertwined with the ethnic-racial relations that coexist in me”; “Categorizing race and racism in the contextualization of the situation of black people in the brazilian society”; “Understanding relevant discussions in the context of Anti-racist Education”; and “To elaborate a pedagogical manual with necessary activities to be worked on in Anti-racist Education”. To this end, Gomes (2005; 2010; 2017; 2020), Munanga (2020), Deus (2020), Moura (2019), Nascimento (2016), Silva (2011), Trindade (2005; 2009) et al. and other intellectuals led me on the path of learning that give support to the study in the theoretical-methodological field and the analysis of the school environment, as well as the construction of a pedagogical notebook that condenses proposals for relevant activities to develop the potential of anti-racist education. In the methodology, I make use (Auto)biographical Research in Education and Research-Action within the qualitative approach focusing on three wheels of conversations with 7 boys and 13 girls, all students from a 4th year Elementary School class, this path allowed me to understand different worldviews and rethink education worked. The study enables enrichment in personal, social, professional, and academic perspectives by raising questions about the bases that direct the commitment of school education in a broad way, breaking with disciplinary limitations, at the same time providing opportunities for reflections based on an anti-racist praxis that is under construction. For the moment, I consider that the expression of the anti-racist struggle in the school space takes into account the re-education of ethnic-racial relations in partnerships with Black Movement entities in such a way that the school takes a stand against racism while understanding itself as an integral part of the dialectic regulation-emancipation and which in historically serving regulation, thus, anti-racist education raises a rethinking of the epistemological bases that lead the educational practice developed in schools, the training of teachers and of all employees and that racism is discussed in the school routine, making it possible its unveiling and deconstruction, providing opportunities for changes in postures.